Expanding Popular Participation in Achieving Solidarity and Social Development Through Waqf Investment Funds - The Experience of the Kingdom of Saudi Arabia - - Cheriak, Rafik (Finance and Business Economies Review, 2022)
Through this research, we tried to show the role played by the endowment - as an Islamic financial institution that represents one of the most important components of the third sector - in supporting solidarity among members of society and achieving social development. To develop endowment funds and activate its role, we find the idea of endowment investment funds, as the latter helps to expand the areas of endowment and encourage individuals to participate in it, leading to the achievement of solidarity and development within society. Arab and Islamic level